Laminated iron product prepared from full-solid-content electron beam curing glue and application of laminated iron product

Through the fully solid electron beam curing glue technology, combined with polybutadiene polyurethane acrylate and other materials, electron beam irradiation curing is solved, and the problems of VOC emission and thermal curing in the traditional coating glue process are achieved efficient and environmentally friendly Production of coated iron products.

CN119505789APending Publication Date: 2025-02-25SUZHOU SANXIN PACKAGING MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411596132.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The traditional metal coating process has problems such as large VOC emissions, subsequent thermal curing, and long processing time, and needs improvement and optimization.

Method used

The coated iron products are prepared using all-solid electron beam curing glue. Through the combination of polybutadiene polyurethane acrylate, silicone polyurethane acrylate, additives and polyfunctional acrylate diluents, electron beam irradiation curing technology is used to simplify Process flow to reduce VOC emissions.

Benefits of technology

It has achieved coated iron products with no VOC emissions, simple operation, shortened curing time, low energy consumption and good environmental protection performance, significantly improving production efficiency and product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505789A_ABST
    Figure CN119505789A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal packaging tin making, and discloses a laminated iron product prepared from full-solid-content electron beam curing glue. The product comprises the following components in parts by weight: 50-90 parts of polybutadiene polyurethane acrylate, 3-25 parts of organic silicon polyurethane acrylate, 0.1-1.5 parts of an auxiliary agent and 5-15 parts of a polyfunctional group acrylate diluent. The specific preparation method of the product comprises the following steps: S1, preparing process aspect; s2, a coating link; s3, fitting characteristics; s4, curing mode; s5, performance expression; and S6, controlling bond fracture and new bond generation under electron beam irradiation. By the adoption of the full-solid-content gluing technology, the coating is a single-component product, easy and convenient to operate, non-toxic, safe, capable of being coated at the normal temperature or heated to 60 DEG C, free of VOC emission in the whole process, environmentally friendly, capable of saving energy, capable of bringing brand new development opportunities to related industries, representative of a novel curing technology, wide in prospect and worthy of being widely applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal packaging canning, and specifically relates to a coated iron product prepared by using all-solid electron beam-cured glue and its application. Background Art

[0002] Laminating adhesive is used to bond film materials to metal substrates and is widely used in the field of metal packaging to improve metal corrosion resistance and surface gloss. Traditional metal laminating adhesives are mostly solvent-based, such as the oily laminating adhesive of patent CN1 12226201A, which produces a large amount of harmful VOC gas during use and is not environmentally friendly. For this reason, water-based technology improvements have emerged, such as patents CN101284978A and CN1 103872088, but they are mainly used in the field of printed flexible packaging. Traditional solvent-based and water-based laminating adhesive processes are complicated, including water-based and acid treatment of metal sheets, coating of glue, low-temperature drying of solvents or water, laminating machine bonding, leveling, and heating or humidification for 48 hours. EB curing and UV curing are often considered to be mainly different in that UV curing requires a photoinitiator. However, in fact, the curing mechanisms of the two are different. UV curing generates free radicals through the decomposition of photoinitiators to initiate polymerization, while EB curing is achieved by direct action of electron beams on the material to achieve curing. Electron beam curing (EB curing) uses electron beam radiation to polymerize and dry the wet coating resin. The mechanism is that the high energy of the electron beam triggers the breakage of material molecules to produce a chemical reaction. The traditional laminating process has problems such as large VOC emissions, the need for subsequent thermal curing, and long processing time, so it needs to be improved and optimized. Summary of the invention

[0003] The purpose of the present invention is to provide a fully solid electron beam cured glue for preparing a coated iron product and its application, so as to solve the problems raised in the above background technology.

[0004] In order to achieve the above object, the present invention provides the following technical scheme: a fully solid electron beam curing glue is used to prepare a coated iron product, the components of which include 50-90 parts of polybutadiene polyurethane acrylate, 3-25 parts of silicone polyurethane acrylate, 0.1-1.5 parts of an auxiliary agent, and 5-15 parts of a multifunctional acrylate diluent. The specific preparation method of the product is as follows:

[0005] S1: Preparation process: The preparation process of the experimental glue is relatively simple. The coating glue can be obtained by weighing the sample in proportion and adding it into the dispersion blending tank, mechanically stirring and filtering. However, the comparative glue may have different preparation processes and requirements;

[0006] S2: Coating: The experimental glue can be coated on the tinplate sheet or PET film by scraping or rolling. The choice is more flexible. The coating thickness is 3-15 microns and the temperature is 25-35℃. The comparative glue may have different coating methods, thickness and temperature requirements.

[0007] S3: Laminating characteristics: In the experiment, the coated iron sheet and the PET film were completely laminated by roller pressing, the transmission speed was 70m / min, the temperature of the pressing roller and the laminating roller was room temperature and the pressure was greater than 0.5MPa;

[0008] S4: Curing method: The experimental glue is cured by placing the laminated iron sample at 60°C and irradiating it with an electron beam, with a voltage of 100-150KV and a total irradiation dose of 10-50KGy;

[0009] S5: Performance: The coated iron samples prepared by the above process need to be tested. Their performance may be different from that of the single-component PUR adhesive (model PUR-XZJ605) produced by Wuxi Wanli Adhesive Materials Co., Ltd. in terms of water boiling resistance, adhesion, impact resistance, etc.;

[0010] S6: Controlling bond breaking and new bond formation under electron beam irradiation: The keys include electron beam energy control, material selection and pretreatment, and environmental control.

[0011] Preferably, the preparation process in S1 refers to weighing various samples in precise proportions to ensure that the ingredients are accurate, then slowly adding the weighed samples into a dispersion blending tank, starting a mechanical stirring device, and continuously stirring at a moderate speed to allow the various ingredients to fully blend. After the stirring is completed, a detailed filtering operation is performed to remove impurities, thereby obtaining high-quality coating glue.

[0012] Preferably, the coating step in S2 refers to the experimental glue showing a high degree of flexibility in the coating step. According to actual needs, the method of scraping or rolling can be selected to coat it on the tinplate sheet or PET film, and the coating thickness is controlled in the range of 3-15 microns, which can not only ensure a good coating effect, but also avoid waste caused by excessive thickness. The temperature is set at 25-35°C to ensure the stable performance of the glue. The comparative glue may have different requirements in these aspects, and its coating method may be relatively simple, and the thickness and temperature restrictions may also be different, thereby affecting the flexibility and efficiency of production.

[0013] Preferably, the bonding feature in S3 refers to the use of roller pressing during the experiment. When the coated iron sheet meets the PET film, a tight fit is achieved through the action of the pressing roller and the bonding roller under a stable state with a transmission speed of 70 m / min. At this time, the pressing roller and the bonding roller are at room temperature, which not only ensures the safety of the operation, but also ensures complete and gapless bonding under a pressure greater than 0.5 MPa.

[0014] Preferably, the curing method in S4 refers to the experimental glue in the curing stage, first placing the bonded coated iron sample in an environment of 60°C, and then using electron beam irradiation curing method, the voltage of the electron beam curing machine is controlled within the range of 100-150KV to ensure that the irradiation intensity is moderate, and the total irradiation dose is set to 10-50KGy to achieve sufficient curing of the glue.

[0015] Preferably, the specific steps of the performance performance in S5 are as follows:

[0016] Step 1: Boiling resistance test: The sample is set at 121℃ in a pressure cooker and boiled for 60 minutes. The sample is considered qualified if there is no whitening, bubbles, or corrosion. The boiling resistance test can simulate high-temperature boiling. Products that pass the test can be used in metal packaging that requires high-temperature sterilization or heating.

[0017] Step 2: Adhesion test: Test according to the method in the test standard GB / T9286-2021 "Scratch test for paint and varnish";

[0018] Step 3: Impact resistance test: Test according to the method in the test standard GB / T1732-2020 "Determination of impact resistance of paint film", and then soak it in 20% copper sulfate. If there is no corrosion point, it is qualified;

[0019] Preferably, the specific steps of controlling bond breaking and new bond generation under electron beam irradiation in S6 are as follows:

[0020] Step 1: Energy control of electron beam: By adjusting the power and scanning speed of the electron beam, the energy and time of irradiation can be precisely controlled, thereby affecting the breaking of chemical bonds and the formation of new bonds. This can only be used for process optimization and fine-tuning under conditions suitable for the adhesive, and cannot play a decisive role;

[0021] Step 2: Material selection and pretreatment: Different materials respond differently to electron beams, so choosing the right material and pre-treating it appropriately is key. Different material choices will result in different application performances. R&D personnel should select and optimize the resin material based on its molecular structure stability. Therefore, material structure optimization is the key to producing high-quality electron beam-cured glue. At the same time, suitable raw materials should be selected for compounding and blending according to different application requirements. By designing a process combination, not only can the advantages of the performance of each component material be maintained, but also the performance of each material can be complemented through compounding and blending to obtain the optimal performance of the combined material. From the perspective of material development, composite materials are full of imagination and innovation:

[0022] Step 3: Environmental control: In addition to the energy of the electron beam, the temperature and humidity of the surrounding environment may also affect the curing process and need to be properly controlled.

[0023] Preferably, based on the above method, the application field of the product is mainly adhesive film materials on the surface of metal plates, including metal coating in the field of metal packaging and canning, and color-coated steel metal plate coated iron, etc.

[0024] The beneficial effects of the present invention are as follows:

[0025] 1. The present invention adopts all-solid adhesive technology, is a single-component product, is easy to operate, non-toxic and safe, can be coated at room temperature or heated to 60°C, has no VOC emissions throughout the process, is environmentally friendly and energy-saving, and uses electron beam curing for curing, which can shorten the curing time to within 0.001-1 second, which is faster than traditional thermosetting and UV curing. This extremely fast curing process can significantly improve production efficiency, greatly shorten the production cycle, and bring new development opportunities to related industries. It is a representative of new curing technology with broad prospects and deserves wide application.

[0026] 2. The electron beam curing technology of the present invention has significant advantages. During the curing process, it only works on the part to be cured, unlike thermal curing which requires heating the entire material, so the energy consumption is low. Moreover, the technology has good environmental performance, can reduce the emission of carbon dioxide and VOC, and has little impact on the environment. Compared with traditional curing methods, electron beam curing performs well in energy saving and environmental protection, and provides a more sustainable solution for related fields.

[0027] 3. The electron beam curing technology of the present invention has obvious advantages. It can achieve uniform curing of the coating, thereby improving the physical and chemical properties of the coating, such as improving hardness, wear resistance and corrosion resistance. This technology is outstanding in improving production efficiency and has a short curing time. At the same time, it reduces energy consumption and avoids the high energy consumption of heating the entire material by thermal curing. In addition, it is environmentally friendly and reduces carbon dioxide and VOC emissions. In short, electron beam curing technology has broad prospects and is an excellent representative of new curing technology, worthy of wide application in multiple fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the overall flow chart of the present invention;

[0029] Figure 2 This is a composition diagram of the product of the present invention;

[0030] Figure 3 This is a performance test diagram of the present invention;

[0031] Figure 4 This is the 50Kg impact diagram of the present invention;

[0032] Figure 5 This is an adhesion test diagram of the present invention;

[0033] Figure 6 The coated iron diagram of the present invention;

[0034] Figure 7 It is a schematic diagram of the structure of the coated iron of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] like Figures 1 to 7 As shown, the embodiment of the present invention provides a fully solid electron beam cured glue to prepare a coated iron product, the components of which include 50-90 parts of polybutadiene polyurethane acrylate, 3-25 parts of silicone polyurethane acrylate, 0.1-1.5 parts of an auxiliary agent, and 5-15 parts of a multifunctional acrylate diluent. The specific preparation method of the product is as follows:

[0037] S1: Preparation process: The preparation process of the experimental glue is relatively simple. The coating glue can be obtained by weighing the sample in proportion and adding it into the dispersion blending tank, mechanically stirring and filtering. However, the comparative glue may have different preparation processes and requirements;

[0038] S2: Coating: The experimental glue can be coated on the tinplate sheet or PET film by scraping or rolling. The choice is more flexible. The coating thickness is 3-15 microns and the temperature is 25-35℃. The comparative glue may have different coating methods, thickness and temperature requirements.

[0039] S3: Laminating characteristics: In the experiment, the coated iron sheet and the PET film were completely laminated by roller pressing, the transmission speed was 70m / min, the temperature of the pressing roller and the laminating roller was room temperature and the pressure was greater than 0.5MPa;

[0040] S4: Curing method: The experimental glue is cured by placing the laminated iron sample at 60°C and irradiating it with an electron beam, with a voltage of 100-150KV and a total irradiation dose of 10-50KGy;

[0041] S5: Performance: The coated iron samples prepared by the above process need to be tested. Their performance may be different from that of the single-component PUR adhesive (model PUR-XZJ605) produced by Wuxi Wanli Adhesive Materials Co., Ltd. in terms of water boiling resistance, adhesion, impact resistance, etc.;

[0042] S6: Controlling bond breaking and new bond formation under electron beam irradiation: The key points include electron beam energy control, material selection and pretreatment, and environmental control;

[0043] In short, the composition of the product includes 50-90 parts of polybutadiene polyurethane acrylate, 3-25 parts of silicone polyurethane acrylate, 0.1-1.5 parts of auxiliary agent, and 5-15 parts of multifunctional acrylate diluent, such as Figure 2 The details are as follows:

[0044] The polybutadiene polyurethane acrylate has the following technical characteristics: a viscosity of 5000 to 30000 mPa.s at 60°C, a Tg of -45°C to 45°C, a functionality greater than or equal to 2, such as BR-641D, BR-641E, BR-643, BR-640D produced by Bomar Specialty Chemicals; CN-310 produced by SARTOMER Chemicals, one or more thereof;

[0045] The silicone polyurethane acrylic has the following technical characteristics: the viscosity at 60°C is 1000-10000 mPa.s, and the functionality is greater than or equal to 2, such as BRS-14320S produced by Bomar Special Chemicals Company, HM-353, HM-2587, HM-5101 produced by Jiangxi Kunlong New Materials Co., Ltd. or one or more thereof;

[0046] The additive is one or more of the leveling agents BYK-300, BYK-306, BYK-301, Afcona3725, 3750, 3031, 3033;

[0047] One or more multifunctional acrylate diluents, such as one or more of SR285NS, SARET SR517NS, SR203NS, SR205NS, SR218NS, SR350NS, and SR834NS from SART0MER Chemical Company.

[0048] Among them, the preparation process in S1 refers to weighing various samples according to precise proportions to ensure that the ingredients are accurate. Then, the weighed samples are slowly added to the dispersion blending tank, and the mechanical stirring device is started. Stirring is continued at a moderate speed to allow the various ingredients to be fully integrated. After the stirring is completed, a detailed filtering operation is performed to remove impurities, thereby obtaining high-quality coating glue.

[0049] First of all, precise weighing ensures the accuracy of the coating glue composition, laying the foundation for the stability of product performance. Adding the sample to the dispersion blending tank and stirring it can fully blend the various ingredients and improve the uniformity and quality of the glue. The meticulous filtering operation removes impurities and obtains pure coating glue, enhancing its use effect, such as improving adhesion and appearance. It also helps to extend the service life of the product and ensure its reliability in different application scenarios.

[0050] Among them, the coating step in S2 refers to the fact that the experimental glue shows a high degree of flexibility in the coating step. According to actual needs, it can be coated on tinplate sheets or PET films by scraping or rolling. The coating thickness is controlled in the range of 3-15 microns, which can not only ensure a good coating effect, but also avoid waste caused by excessive thickness. The temperature is set at 25-35°C to ensure the stable performance of the glue. The comparative glue may have different requirements in these aspects. Perhaps its coating method is relatively simple, and the thickness and temperature restrictions may also be different, which affects the flexibility and efficiency of production.

[0051] The coating process provides two methods: scraping and rolling, which greatly increases the flexibility of production and can meet the needs of different scenarios. The coating thickness range of 3-15 microns can not only ensure the lamination effect but also avoid waste, which is beneficial to cost control. The temperature of 25-35°C ensures the stability of the glue performance and improves product quality. In contrast, the comparative glue may affect the production flexibility and efficiency due to the single coating method, different thickness and temperature restrictions, which highlights the advantages of this experimental glue in these aspects.

[0052] Among them, the bonding feature in S3 refers to the fact that during the experiment, when the coated iron sheet meets the PET film, a roller pressing method is used. Under a stable state with a transmission speed of 70m / min, a tight fit is achieved through the action of the pressing roller and the bonding roller. At this time, the pressing roller and the bonding roller are at room temperature, which not only ensures the safety of the operation, but also ensures a complete and gapless bonding under a pressure greater than 0.5MPa.

[0053] Lamination characteristics: First of all, the roller pressing method is easy to operate and efficient, which can ensure the stable lamination of the iron sheet and the PET film. The transmission speed of 70m / min ensures the continuity and efficiency of production. Lamination at room temperature ensures safe operation and avoids the risks that may be caused by high temperature. The pressure is greater than 0.5MPa, which makes the lamination complete and gapless, improves the quality and durability of the laminated products, and reduces the defective rate caused by poor lamination.

[0054] Among them, the curing method in S4 refers to the experimental glue in the curing stage, first placing the bonded coated iron sample in an environment of 60°C, and then using electron beam irradiation curing method, the voltage of the electron beam curing machine is controlled within the range of 100-150KV to ensure that the irradiation intensity is moderate, and the total irradiation dose is set to 10-50KGy to achieve sufficient curing of the glue.

[0055] The curing method is to place the coated iron sample in a 60℃ environment and then perform electron beam irradiation curing. The moderate temperature of 60℃ can assist the curing process to a certain extent and is more energy-efficient. The voltage range of 100-150KV and the total irradiation dose of 10-50KGy of the electron beam curing machine ensure that the irradiation intensity is moderate, which can achieve full curing of the glue and improve the stability and durability of the product. Compared with traditional curing methods, electron beam curing is fast, which greatly shortens the production cycle and improves production efficiency.

[0056] The specific steps of the performance performance in S5 are as follows:

[0057] Step 1: Boiling resistance test: The sample is set at 121℃ in a pressure cooker and boiled for 60 minutes. The sample is considered qualified if there is no whitening, bubbles, or corrosion. The boiling resistance test can simulate high-temperature boiling. Products that pass the test can be used in metal packaging that requires high-temperature sterilization or heating.

[0058] Step 2: Adhesion test: Test according to the method in the test standard GB / T9286-2021 "Scratch test for paint and varnish";

[0059] Step 3: Impact resistance test: Test according to the method in the test standard GB / T1732-2020 "Determination of impact resistance of paint film", and then soak it in 20% copper sulfate. If there is no corrosion point, it is qualified;

[0060] Performance performance test of water boiling resistance, adhesion test and impact resistance test, according to Figure 3 and Figure 3 The comparative test results show that Figure 3 After construction, the adhesion is all level 1, the water boiling resistance is not white, and there are no bubbles after the film is boiled. The 50Kg impact is for example 2, example 4, and example 5, all of which are level 1, with good mechanical processing performance. The above performance shows that Figure 3 It can be used for food packaging applications to ensure that the product remains stable in actual applications such as high-temperature sterilization or heated metal packaging scenarios. The qualified standards of no whitening, no bubbles, and no corrosion ensure the reliability and safety of the product, extend the service life of the product, and make it less likely for the film to fall off during use, thereby improving the quality and durability of the product, ensuring that the product remains in good condition under external impact and possible corrosive environments, and providing protection for the product in various complex usage environments.

[0061] The specific steps of controlling bond breaking and new bond generation under electron beam irradiation in S6 are as follows:

[0062] Step 1: Energy control of electron beam: By adjusting the power and scanning speed of the electron beam, the energy and time of irradiation can be precisely controlled, thereby affecting the breaking of chemical bonds and the formation of new bonds. This can only be used for process optimization and fine-tuning under conditions suitable for the adhesive, and cannot play a decisive role;

[0063] Step 2: Material selection and pretreatment: Different materials respond differently to electron beams, so choosing the right material and pre-treating it appropriately is key. Different material choices will result in different application performances. R&D personnel should select and optimize the resin material based on its molecular structure stability. Therefore, material structure optimization is the key to producing high-quality electron beam-cured glue. At the same time, suitable raw materials should be selected for compounding and blending according to different application requirements. By designing a process combination, not only can the advantages of the performance of each component material be maintained, but also the performance of each material can be complemented through compounding and blending to obtain the optimal performance of the combined material. From the perspective of material development, composite materials are full of imagination and innovation:

[0064] Step 3: Environmental control: In addition to the energy of the electron beam, the temperature and humidity of the surrounding environment may also affect the curing process and need to be properly controlled.

[0065] Energy control of the electron beam that controls bond breaking and new bond generation under electron beam irradiation, material selection and pretreatment, and environmental control can help achieve more precise adjustment of the curing effect, improve the stability of product quality, and make material structure optimization the key to producing high-quality electron beam-cured adhesives. By compounding and blending different structural raw materials, the performance advantages of each material can be brought into play and complement each other to obtain the optimal combined performance, providing broad space for product innovation. Proper control of the surrounding environment temperature, humidity, etc. can reduce the adverse effects of environmental factors on the curing process, ensure the stability and reliability of the curing process, and further improve product quality.

[0066] Among them, based on the above method, the application field of this product is mainly adhesive film materials on the surface of metal plates, including metal coating in the field of metal packaging and canning, and color steel metal plate coated iron, etc.

[0067] This product uses all-solid adhesive technology combined with electron beam curing. It has the advantages of easy operation, non-toxic and safe, no V0C emissions, and fast curing speed. It only works on the part that needs to be cured, has low energy consumption and is environmentally friendly, can improve coating performance, and compared with traditional curing methods, it performs well in energy saving and environmental protection, bringing new opportunities to related industries. It is a representative of new curing technology with broad prospects and deserves wide application.

[0068] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fully solid electron beam cured glue for preparing a coated iron product, characterized in that: The composition of the product includes 50-90 parts of polybutadiene polyurethane acrylate, 3-25 parts of silicone polyurethane acrylate, 0.1-1.5 parts of auxiliary agent, and 5-15 parts of multifunctional acrylate diluent. The specific preparation method of the product is as follows: S1: Preparation process: The preparation process of the experimental glue is relatively simple. The sample is weighed in proportion and added into the dispersion blending tank. After mechanical stirring, the coating glue can be obtained by filtering. S2: Coating: The experimental glue can be coated on the tinplate sheet or PET film by scraping or rolling. The choice is more flexible. The coating thickness is 3-15 microns and the temperature is 25-35℃. S3: Laminating characteristics: In the experiment, the coated iron sheet and the PET film were completely laminated by roller pressing, the transmission speed was 70m / min, the temperature of the pressing roller and the laminating roller was room temperature and the pressure was greater than 0.5MPa; S4: Curing method: The experimental glue is cured by placing the laminated iron sample at 60°C and irradiating it with an electron beam, with a voltage of 100-150KV and a total irradiation dose of 10-50KGy; S5: Performance: The coated iron samples prepared by the above process need to be tested, and their performance is compared with the single-component PUR adhesive (model PUR-XZJ605) produced by Wuxi Wanli Adhesive Materials Co., Ltd.; S6: Controlling bond breaking and new bond formation under electron beam irradiation: The keys include electron beam energy control, material selection and pretreatment, and environmental control.

2. The method of preparing a coated iron product by using a fully solid electron beam cured glue according to claim 1, characterized in that: The preparation process in S1 refers to weighing various samples according to precise proportions to ensure that the ingredients are accurate. Then, the weighed samples are slowly added to the dispersion blending tank, and the mechanical stirring device is started. Stirring is continued at a moderate speed to fully blend the various ingredients. After the stirring is completed, a detailed filtering operation is performed to remove impurities, thereby obtaining high-quality coating glue.

3. The method of preparing a coated iron product by using a fully solid electron beam cured glue according to claim 1, characterized in that: The coating step in S2 refers to the high flexibility of the experimental glue in the coating step. According to actual needs, the method of scraping or rolling is selected to coat it on the tinplate sheet or PET film. The coating thickness is controlled in the range of 3-15 microns, which can not only ensure a good coating effect, but also avoid waste caused by excessive thickness. The temperature is set at 25-35°C to ensure the stable performance of the glue. The comparative glue has different requirements in these aspects. Its coating method is relatively single, and the thickness and temperature restrictions are different, which affects the flexibility and efficiency of production.

4. The method of preparing a coated iron product by using a fully solid electron beam cured glue according to claim 1, characterized in that: The bonding feature in S3 refers to the fact that during the experiment, when the coated iron sheet meets the PET film, a tight bonding is achieved through the action of the pressing roller and the bonding roller at a stable transmission speed of 70 m / min. At this time, the pressing roller and the bonding roller are at room temperature, which not only ensures the safety of the operation, but also ensures complete bonding without gaps under the condition of a pressure greater than 0.5 MPa.

5. The method of preparing a coated iron product by using a fully solid electron beam cured glue according to claim 1, characterized in that: The curing method in S4 refers to the curing stage of the experimental glue. The laminated iron sample is first placed in an environment of 60°C, and then electron beam irradiation curing is adopted. The voltage of the electron beam curing machine is controlled within the range of 100-150KV to ensure that the irradiation intensity is moderate. The total irradiation dose is set to 10-50KGy to achieve sufficient curing of the glue.

6. The method of preparing a coated iron product by using a fully solid electron beam cured glue according to claim 1, characterized in that: The specific steps of the performance of S5 are as follows: Step 1: Boiling resistance test: The sample is set at 121℃ in a pressure cooker and boiled for 60 minutes. The sample is considered qualified if there is no whitening, bubbles, or corrosion. The boiling resistance test simulates high-temperature boiling. Products that pass the test can be used in metal packaging that requires high-temperature sterilization or heating. Step 2: Adhesion test: Test according to the method in the test standard GB / T9286-2021 "Scratch test for paint and varnish"; Step 3: Impact resistance test: Test according to the method in the test standard GB / T1732-2020 "Determination of impact resistance of paint film", then soak in 20% copper sulfate, and it is qualified if there is no corrosion point.

7. The method of preparing a coated iron product by using a fully solid electron beam cured glue according to claim 1, characterized in that: The specific steps of controlling bond breaking and new bond generation under electron beam irradiation in S6 are as follows: Step 1: Energy control of electron beam: By adjusting the power and scanning speed of the electron beam, the energy and time of irradiation are precisely controlled, thereby affecting the breaking of chemical bonds and the formation of new bonds; Step 2: Material selection and pretreatment: R&D personnel select and optimize the resin material based on its molecular structure stability, and design process combinations to maintain the advantages of each component material. They can then complement the performance of each material through compounding and blending to obtain the optimal performance of the combined material.

8. The method for preparing a coated iron product and its application by using a fully solid electron beam cured glue according to claims 1-7, characterized in that: Based on the above method, the application field of this product is mainly adhesive film materials on the surface of metal plates, including metal coating in the field of metal packaging and canning, and colored steel metal plate coated iron.

Citation Information

Patent Citations

  • Waterborne dry-type laminated adhesive and polymerization method threreof

    CN101284978A

Cited By

  • Equivalence evaluation method for testing fracture behavior of irradiation metal material based on small sample

    CN121231208A